Human Response Is Lognormal; Plan on Waiting If You Want Reliability. (January 2013) - Sheridan, Thomas B.
Human response times fit a lognormal probability function, which poses severe constraints on the time a system designer must allow to accommodate a significant fraction of respondents; for example, 6 standard deviations for 95% confidence and 11 standard deviations for 99% confidence. When a human operates in series with machine elements, there may be no justification for demanding a quick response from the machine.